1983
DOI: 10.1002/smj.4250040404
|View full text |Cite
|
Sign up to set email alerts
|

Type of entrepreneur, type of firm, and managerial motivation: Implications for organizational life cycle theory

Abstract: Miner Sentence Completion Scale measures of managerial motivation for a sample of Oregon entrepreneurs were compared with interview data on entrepreneur and firm type using a system of differentiation derived from the Enterprising Man (Collins, Moore and Unwalla, 1964) research. Certain relationships between aspects of managerial motivation and firm expansion and growth were found. In addition, the overall level of managerial motivation among the entrepreneurs relative to corporate managers was found to be low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
1
11

Year Published

1990
1990
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(140 citation statements)
references
References 10 publications
3
125
1
11
Order By: Relevance
“…Loosely construed, they can be seen as akin to the "craftsman" type of entrepreneur (Smith and Miner, 1983) but these parables are not distinctively entrepreneurial. Only one passage in the Zhuangzi is.…”
Section: A Knack For Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Loosely construed, they can be seen as akin to the "craftsman" type of entrepreneur (Smith and Miner, 1983) but these parables are not distinctively entrepreneurial. Only one passage in the Zhuangzi is.…”
Section: A Knack For Entrepreneurshipmentioning
confidence: 99%
“…47-50) this passage is a metaphor for cognitive processes, but business scholars will be struck by how well this trader exemplifies "opportunistic" entrepreneurship (Smith and Miner 1983) as theorized by "Austrian school" economists (Kirzner, 1973: 198), by sociologists such as Burt (1992), and anthropologists such as Barth (1967). In these approaches, opportunities for profit are generated by discrepancies of evaluation across social and cultural boundaries, geographic distance, or time.…”
Section: A Knack For Entrepreneurshipmentioning
confidence: 99%
“…As such, its focus shifts to seeking congruence or fi t among key variables. This line of studies explores factors, which originate from the environment, structure, and strategy, with the investigation centered on how these factors impinge on the context (e.g., Covin and Slevin, 1989;Gartner, 1985;Miller, 1983;Smith and Miner, 1983). 3 Although it has a better, often cogent rationale behind the explanation, the contingency approach fails to give answers to the question of why a reasonable person would not seek a premium for an investment riskier than the public investment index.…”
Section: An Answer From the Contingency Approachmentioning
confidence: 99%
“…Two studies that postulate organizational life cycle theories of the firm have attempted to relate psychological characteristics of entrepreneurs to the adaptation needed during a firm's transition, but neither study examined technological companies. [4,17] Only the few works cited below have been found that applied these models toward data collection on technical firms.…”
Section: The Relevant Literaturementioning
confidence: 99%
“…Two studies that postulate organizational life cycle theories of the firm have attempted to relate psychological characteristics of entrepreneurs to the adaptation needed during a firm's transition, but neither study examined technological companies. [4,17] Only the few works cited below have been found that 5 applied these models toward data collection on technical firms. Van de Ven [21] classifies the research on the creation of organizations into entrepreneurial (focusing upon personal characteristics of founders), ecological (focusing upon shifts in organization populations and their reasons), and organizational (focusing upon managerial processes involved in initiation and early development).…”
mentioning
confidence: 99%